Bayesian estimates of genetic parameters for reproductive traits in Nellore cows raised on pasture in tropical regions - Ulhôa Magnabosco Cláudio; Brito Lopes, Fernando; de Magalhaes Rosa, Guilherme Jordão; Sainz, Roberto Daniel (Revista Colombiana de Ciencias Pecuarias, 2016)
Nellore cows are well adapted to tropical conditions, and they have good maternal ability as well as long and prolific reproductive life. Objective: to estimate (co)variances and genetic parameters for calving interval (CI), age at first calving (AFC), gestation length (GL), and days open (DO) in Nellore cows. Methods: covariance components and genetic parameters were estimated using multi-trait Bayesian procedures. Results: three traits had low but statistically significant heritabilities, averaging 0.05, 0.10, and 0.04 for CI, GL, and DO, respectively, whereas age at first calving had a higher heritability (0.36). The permanent environmental effects for CI, GL, and DO were also low, averaging 0.08, 0.07, and 0.15, respectively. The genetic correlations between AFC and CI, AFC and GL, AFC and DO, GL and CI, CI and DO, GL and DO were 0.20, 0.12, 0.11, 0.02, 0.92, and -0.21, respectively. Selection for shorter CI would contribute towards decreasing DO. However, selection for decreased GL could result in a greater number of DO. Despite the favorable genetic correlations, the direct selection responses for these traits would be low. Conclusion: reproductive traits are strongly influenced by environmental effects. Changes in management and environmental factors could rapidly improve reproductive performance of Polled Nellore herds. Genetic selection for these traits should produce a much slower but permanent response.